Prevalence of Cardiovascular Risk Factors in Apparently Healthy Urban Adult Population of Kathmandu - Anil, Om Murti; Yadav, Randhir Sagar; Shrestha, Nitesh; Koirala, Sachit; Shrestha, Shumneva; Nikhil, Om Murti; Baidar, Manisha; Chaudhary, Nabin; Jaishwal, Chandni; Yadav, Navin Sagar; Mahara, Aabhushan Bikram; Jha, Roshan Kumar; et al. (Journal of Nepal Health Research Council, 2019)
Background: Cardiovascular diseases account for most deaths and major proportion of disabilities worldwide. Major cardiovascular risk factors are implicated in almost 75% of cardiovascular diseases. There has been a rapid increase in prevalence of such risk factors in apparently healthy young adults of urban population. This study aimed to find prevalence of such risk factors in order to implement preventive strategies against cardiovascular diseases in our setting.Methods: A free heart camp was organized following wide dissemination of information through print, online, TV, radio and social media. Pretested data collection tool was used by trained enumerators using standard guidelines and calibrated devices. Demographic, anthropometric, physical examination and blood investigation data were obtained. Standard guidelines were followed to define and categorize the obtained information. Data was analyzed using SPSS V20.Results: A total of 5530 participants were enrolled after carefully applying inclusion and exclusion criteria. Mean age of study population was 38.14±13.03 years. There were 3298 (59.6%) males with mean age of 37.67±12.99 years and 2232 (40.4%) females with mean age of 38.84±13.05 years. Majority of study population (29.6%) belonged to 30-39 years age group. Prevalence of tobacco and alcohol consumption was 29.3%(95%CI:28.1-30.5) and 32.7%(95%CI:31.5-34.) respectively. Prevalence of inadequate fruits and vegetables intake, low physical activity and overweight or obesity was 75.4%(95%CI:74.3-76.6), 61.1%(95%CI:59.8-62.4) and 41.3%(95%CI:40.0-42.6) respectively. Prevalence of hypertension, diabetes and dyslipidemia was 26.4%(95%CI:25.3-27.6), 5.3%(95%CI:4.7-5.9) and 86.9%(95%CI:85.9-87.7) respectively. These results were statistically significant in both age and sex based distribution.Conclusions: Prevalence of major cardiovascular risk factors in apparently healthy adult population of Kathmandu Valley was high. Dyslipidemia, unhealthy diet, physical inactivity and overweight or obesity were most prevalent cardiovascular risk factors. Keywords: Cardiovascular risk factors; healthy adults; prevalence; urban population.